The Importance of Widespread Temperature Conditions on Breakup Characteristics: The Case of Sagavanirktok River, Alaska, USA - Horacio Toniolo; Eric LaMesjerant; Alex Lai; John Keech; Joel Bailey (Water, 2023)
Daily average springtime air temperatures from four weather stations distributed along north–south and nearly east–west directions within or on the divide of the Sagavanirktok River watershed in Arctic Alaska were studied and compared with discharge measurements and field observations made from 2015 to 2021 during breakup. The results indicate that under widespread air temperature events, during El Niño, rapid and dynamic breakup can occur (promoting sediment transport along the stream), while during La Niña, slow and thermal breakup can be expected. Due to these climate pattern effects, open channel conditions (i.e., ice-free channels) are reached earlier (18 May 2015) during El Niño and later (7 June 2021) during La Niña.